A Fractal Dimensional Analysis of Vernacular House Façades in Indonesia: Rumah Gadang and Uma - Johanita Anggia Rini (Departement of Architecture, Universitas Islam Indonesia, 2024)
Vernacular house façades have distinct visual characteristics as a reflection of the factors that influence vernacular architecture, one of which is how the locals perceive and interpret aesthetics. This study attempts to quantitatively examine the aesthetic qualities of the façades of two vernacular houses, namely Rumah Gadang from West Sumatra, western Indonesia, and Uma from Sumba Island, eastern Indonesia. Both have very different geographical conditions, cultural, and historical backgrounds. The fractal dimension analysis is used by breaking down the façade into 5 layers of architectural attribute; silhouette, main tripartite, structure, façade components, and material texture. Using the box-counting method, it is known which layer is the biggest contributor to the visual complexity of the façades. Based on the calculations, it is concluded that there are differences in the degree and proportion of visual complexity in the case of the two houses. The façade of Rumah Gadang has higher visual complexity than Uma. Material texture is the most dominant contributor to visual complexity of both houses. In Rumah Gadang, the façade components greatly contribute to visual complexity, while in Uma the silhouette has a big influence. This finding can be attributed to the way the homeowners place importance on the façade and the house in its respective social system, or even the development of civilization behind the two houses. It is also found that subjective-qualitative visual observation and philosophical approach do not always correspond with the result of mathematical calculation. Keywords: façade; fractal analysis; fractal dimension; Indonesian vernacular house; rumah gadang; uma; visual complexity